Promotion of youth development programme through entrepreneurial skills in the Niger delta - Ogu, Sokari Jusih (YAYASAN MITRA PERSADA NUSANTARA, 2025)
The Nigerian economy, particularly in the Niger Delta region, is characterized by a heavy reliance on government-driven investments and employment creation, with limited private sector entrepreneurship. This dependence has hindered economic diversification and sustainable development. This study explores the promotion of youth development through entrepreneurial skills in the Niger Delta as a strategy for fostering sustainable development. The study aims to examine the roles and types of entrepreneurship, identify the goals of entrepreneurs, and analyse effective models for entrepreneurial skill acquisition. It also highlights the importance of employability and entrepreneurship skills in addressing youth unemployment in the Niger Delta. The research employs a qualitative approach, drawing from existing literature and case studies to assess the current state of entrepreneurship in the region. It examines training models, skill acquisition programs, and their effectiveness in enhancing youth employment opportunities. Findings reveal that the limited presence of private sector entrepreneurship in the Niger Delta has perpetuated overdependence on government-driven employment. The study identifies critical gaps in entrepreneurial training and skill acquisition frameworks. It highlights the need for targeted interventions, including practical entrepreneurship education, mentorship programs, and access to financial resources, as essential components of a sustainable development strategy. The study concludes that promoting entrepreneurial skills among youths in the Niger Delta is crucial for reducing unemployment and fostering economic self-reliance. It recommends the integration of entrepreneurship into formal education, the establishment of public-private partnerships, and the provision of financial and institutional support to young entrepreneurs. By addressing these challenges, the Niger Delta can transition from an overreliance on government employment to a diversified, sustainable economy driven by youth-led entrepreneurship initiatives.